ANALISA SIFAT MEKANIK UJI TARIK LOGAM PADUAN KUNINGAN 60/40 (Cu Zn), BAJA KARBON 0,4% (OIL QUENCH-TEMPER) DAN PERUNGGU ALUMINIUM - Feddy Wanditya Setiawan (Program Studi Teknik Otomotif, Politeknik Hasnur, 2021)
This study aims to determine the results of tensile testing of three types of alloys that are usually used as materials for various automotive components and other machinery products, namely brass 60/40 (Cu Zn), 0.4% carbon steel (oil quench-tempered) and aluminum bronze. The results showed that brass metal 60/40 (Cu Zn) had a yield strength of 186.48 N/mm2, a ultimate tensile strength of 260.12 N/mm2 and a final strain of 80.13%. Bronze aluminum yield strength of 331.39 N/mm2, ultimate tensile strength of 488.29 N/mm2 and final strain of 30.88%. Meanwhile, 0.4% carbon steel (oil quench-tempered) has a yield strength of 495.30 N/mm2, a ultimate tensile strength of 689.09 N/mm2 and a final strain of 28.06%. Aluminum bronze is much more brittle than brass metal because there is no visible shrinkage in the diameter of the specimen until the end of the specimen is fractured. 0.4% carbon steel is seen linearly undergoing elastic deformation then plastic deformation and shrinkage of the specimen diameter until it approaches fracture. From the three test specimens, it is known that brass metal has the highest level of ductility because it has the largest plastic deformation (ductile fracture) or the final strain value reaches 80.13%.